POLA KEMAJUAN SELEKSI PADA CABAI RAWIT (Capsicum frutescens L) - Rosminah, Rosminah; Syukur, Muhamad; Maharijaya, Awang (Agros Journal of Agriculture Science, 2024)
Public demand for cayenne pepper is high, so it is necessary to improve the quantitative characteristics of chilies, one of which is by selecting. This research aims to obtain information regarding the mean and interval values of several quantitative characters, inbreeding depression, heritability values, and selection progress from five generations resulting from crossing two cayenne pepper parents. The genetic material used consisted of two chili parents, namely the genotype IPB C321 (female parent), and IPB C290 (male parent) along with the results of crossing the two in the F2, F3, F4, and F5 generations with a total of 580 individual plants. The research results showed that based on the mean value between the F2 to F5 generations, there was an increase in the observed characters except at harvest age. The observed characters did not experience inbreeding depression. The heritability value in the narrow sense shows the high criteria for fruit length characters in the observed generation, fruit weight per plant and weight per fruit in the F2 generation, number of fruit per plant in the F2 and F3 generations, and fruit diameter in the F3 and F4 generations. Other generations have heritability values in the narrow sense of low and medium criteria. In general, the progress of selection for quantitative characters in the five chili generations studied showed a decline, although there were decreases and increases in the generations and characters observed.